2010
DOI: 10.1603/an09131
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Size and Oviposition Depths ofRomalea microptera(Orthoptera: Acrididae) is Associated with Different Soil Conditions

Abstract: Intraspecific geographic variation in morphology and behavior can be indicative of populations that are adapted to local environmental conditions. Heterogeneity in the abiotic environment, such as soil conditions, can be an important driver of local adaptation. In south Florida, mean body sizes in populations of the lubber grasshopper Romalea microptera (Beauvois) (Orthoptera: Acrididae), increase from west to east. We tested how body size variation, population origin, and soil physical characteristics are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This possibility is supported by our recent study on P. vittatum that reported a positive correlation between soil moisture and relative abundance along the same gradient (Yadav et al, ). Soil moisture significantly influences the viability of offspring in grasshoppers (Herrmann, Ko, Bhatt, Jannot, & Juliano, ) and may affect local population distributions via the presence of parasitic nematodes and entomopathogenic fungi of P. vittatum (Clift & Baker, ; Milner & Prior, ) and in other Orthoptera (Barbercheck, ). Notably, of all tested variables, latitude had the highest number of SNP associations ( n = 100, unique = 84), which probably reflects a combination of environmental changes along the sampled latitudinal gradient.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by our recent study on P. vittatum that reported a positive correlation between soil moisture and relative abundance along the same gradient (Yadav et al, ). Soil moisture significantly influences the viability of offspring in grasshoppers (Herrmann, Ko, Bhatt, Jannot, & Juliano, ) and may affect local population distributions via the presence of parasitic nematodes and entomopathogenic fungi of P. vittatum (Clift & Baker, ; Milner & Prior, ) and in other Orthoptera (Barbercheck, ). Notably, of all tested variables, latitude had the highest number of SNP associations ( n = 100, unique = 84), which probably reflects a combination of environmental changes along the sampled latitudinal gradient.…”
Section: Discussionmentioning
confidence: 99%
“…4b ). Soil can control insect abundances via influencing life-history traits of phytophagous insects, such as egg laying, nymphal development (as shown in the lubber grasshopper, Romalea microptera (Beauvois) (Orthoptera: Acrididae); Herrmann et al 2010 ), or via regulation of habitat resources ( McColloch and Hayes 1922 ) and controlling the growth of suitable food resources ( Miao et al 2018 ). Soil moisture content can support vegetation growth; this may compromise egg laying in P. vittatum because females preferentially lay egg pods in patches of bare ground ( Clark 1967 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foliage cover is important for egg laying in this species, as eggs are laid in open areas with bare ground between vegetation patches ( Clark 1967 ). In addition, soil properties such as soil moisture and soil type have been shown to influence density ( Miao et al 2018 ), oviposition, and therefore further offspring viability in grasshoppers ( Herrmann et al 2010 ). Wind speed was chosen because wind is beneficial for passive dispersal of insects ( Drake 1994 , Venette and Ragsdale 2004 ) and may aid in the colonization of new areas by facilitating long-distance dispersal ( Anderson et al 2010 , Colombari and Battisti 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, in the current study we found that soil (i.e., soil pH and soil bulk density) and terrain variables were associated with signatures of selection in Kosciuscola grasshoppers (Tables 1 and 2). In grasshoppers, soil properties can influence the viability of offspring by affecting oviposition and can regulate the prevalence of parasitic nematodes and entomopathogenic fungi (Herrmann et al, 2010;Milner & Prior, 1994). Our previous study on another grasshopper species (Phaulacridium vittatum) found an important effect of soil moisture on site relative abundance (Yadav et al, 2018), and soil moisture and pH were associated with loci under selection using EAA (Yadav et al, 2019 (Kearney et al, 2009).…”
Section: Microgeographical Adaptationmentioning
confidence: 97%